Quantifying Escherichia Coli Release from Soil under High-Intensity Rainfall - Ling, Teck Yee; Jong, H.J.; Kasing, Apun; Wan Sulaiman, W.H (American Society of Agricultural and Biological Engineers, 2009)
Bacterial loading in surface runoff can only be reasonably assessed or predicted with quantitative knowledge of the release of bacteria from the soil under different rainfall conditions. Most studies of bacterial movement were conducted under rainfall intensities of less than 44 mm h-1. However, in the tropics, intensities higher than 44 mm h-1 are frequent. In this study, Escherichia coli release from the soil into surface runoff and its distribution in the soil under the impact of heavy rainfall (95 mm h-1) of different durations were investigated. Results of simulated heavy rainfall of different durations on gently sloping grass plots with spray-applied E. coli indicated that E. coli was released with relative ease, resulting in contaminated runoff. Runoff E. coli concentrations ranged from 2.09 log(CFU) mL -/ in 5 mill simulated rainfall events to 4.45 10g(CFU) mL -/ in 15 min simulated rainfall events. The first simulated rainfall events after spray applications J. ·roduced the highest concentration ofE. coli in the runoff. Runoff loss accounted for 0.001% of the total applied E. coli in 5 mill rainfall events and 2.1 % in 15 min rainfall events. Total solids explailled 28% of the variation in the concentrations and 14% of the total loadings. E. coli concentration in the surface centimeter of the soil explained 80% to 89% of the variations ill runoff concentrations and loadings with regression slope of less than ullity. Such quantitative relatiollships have the potential to predict runoff E. coli concentrations under high-intensity rainfall events.